Kompatibilitas Islam dan Demokrasi: Tantangan dan Hambatan Demokratisasi di Dunia Islam - Abdul Jalil (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2020)
[THE COMPATIBILITY OF ISLAM AND DEMOCRACY: CHALLENGES AND OBSTACLES OF DEMOCRATIZATION IN ISLAMIC WORLD] This study aims to find out whether Islam and democracy are compatible, as well as how the challenges and obstacles of democratization in the Muslim world. This research is in the form of a pure library (library research) using descriptive qualitative methods. Data analysis of the discussion uses the inductive approach, which is to draw general conclusions from specific conclusions. In principle, not all democratic teachings are relevant to Islamic teachings. When democracy becomes a commitment for the state to be put into practice, then all aspects of life cannot be separated from a touch of democracy, including religion. In Muslim countries, especially Asia and North Africa, religious democracy does not necessarily go hand in hand with the practice of political democracy. Doctrinally, Islam and democracy are two different things, but substantively there are democratic principles that are compatible with Islamic teachings. The principle of justice in law enforcement, equality in community life, nation and state, as well as freedom of opinion, religion, and belief. These principles are ideally contained in a written document, the Medina Charter